Complex Above- and Below-Ground Growth Responses of Two Urban Tree Species Following Root, Stem, and Foliage Damage—An Experimental Approach - Vitali, Valentina; Ramirez, Jorge A.; Perrette, Guillaume; Delagrange, Sylvain; Paquette, Alain; Messier, Christian (Frontiers in Plant Science, 2019)
Abstract Urban trees are subjected to numerous biotic and mechanical damage, which can affect their growth rates and health. However, for most species, a systematic analysis of tree above- and below-ground growth reactions to a variety of damages is still lacking. Under a fully factorial experimental setup, using two common urban trees (Celtis occidentalis, Fraxinus pennsylvanica), we tested the effects of various degrees of frequently occurring damage as defoliation, root reduction and stem injuries for a total of 18 treatments. We hypothesized that i) an increasing amount of damage would proportionally negatively affect both root and stem growth, ii) there would be a lag or lasting effect on growth, and iii) both species would react similarly to the treatments. Contrary to our expectation, increasing levels of single or combined damage did not have an incremental effect on either stem or root growth. Although Celtis was significantly less vigorous than Fraxinus, it did not react strongly to damage treatments compared to the control. Interestingly, Celtis that experienced stem damage alone or in combination with other damages showed higher growth rates than the control. For Celtis, root injury was the treatment having the most impact, decreasing both root and stem growth consistently throughout the 5 years following treatments, whereas defoliation decreased growth only in the first two years. All damage treatments negatively affected stem and root growth of Fraxinus trees. Stem growth was affected the most by defoliation in the first year following the treatment, while root injury became the driving factor in subsequent years. For both species, stem injury showed the least influence on growth rates. The control and low-level damage treatments often affected growth rates in a similar way, suggesting that low-intensity stress triggers compensatory reactions stimulating photosynthetic rates and nutrient utilization. The slower-growing tree species, Celtis, showed a less negative reaction to all damage treatments compared to Fraxinus. This study illustrates that various types of above- and below-ground injuries do not have a simple additive effect on tree growth and that trees are capable of compensating for the loss of foliage, roots, or phloem to meet their metabolic demand.